Hydrothermal synthesis of lead zirconate titanate (PZT) and lead lanthanum zirconate titanate (PLZT) nanopowders - Nualpralaksana S. (2014)
Nano- to micron-sized powders of PZT and PLZT were hydrothermally synthesized at temperatures of 125 and 140°C, pressures of 500 and 600 kPa, and holding times of 3 and 5 h. It was found that calcining the as-synthesized materials at 800°C for 2 h produced fine spherical powders (200...300 nm) of PZT with a 1:1 mass ratio of a rhombohedral PbZr0,58Ti0,42O3 and a tetragonal PbZr0,52Ti0,48O3 phase as well as powders (100...1 000 nm) of PLZT with a 2:1 mass ratio of a tetragonal (Pb,La) (Zr0,52Ti0,48)O3 and a cubic (Pb0,9La0,1) (Zr0,65Ti0,35)O3 phase.